A INTEGRAÇÃO DA BIBLIOTECA ESCOLAR E TECNOLOGIAS EDUCACIONAIS NA PRÁTICA PEDAGÓGICA: um estudo com professores dos Anos Iniciais do Ensino Fundamental na Unidade de Educação Básica Mariana Pavão - MARINHO, Danielle Cabral (2024)
The dialog between the school, library and technologies can be seen as an interdependent and inseparable part of the educational process, so this research addresses the integration of the school library and educational technologies in the pedagogical practice of teachers of the Early Years of Primary School, with the public institution Unidade de Educação Básica Mariana Pavão, belonging to the Municipal Education Network of São Luís (MA), as its locus. My interest in the subject stemmed from the following problem: how can the school library be integrated with educational technologies for the pedagogical practice of 3rd and 4th grade elementary school teachers? This question led to the research objective of investigating how to integrate the school library and educational technologies for pedagogical practice, with a view to producing an E-book containing pedagogical guidelines to support 3rd and 4th grade elementary school teachers. In order to achieve the objectives, an applied, exploratory and descriptive study was carried out, based on the technical procedures of bibliographical and field research, adopting a qualitative research approach. A systematic literature review was carried out covering 2020 to 2023 in four databases: Google Scholar, CAPES, SciELO and BDTD, as well as consultations in books, official documents and Education and Librarianship regulations. With regard to the field research, questionnaires were used to collect data from (1) school manager, (1) pedagogical coordinator and (3) teachers. The results were structured into categories and discussed in the light of the theoretical framework. These made it possible to understand that the integration of the library and technologies contributes significantly to teachers' pedagogical practice, through the implementation of differentiated teaching strategies for the development of reading and writing skills, with an emphasis on student protagonism. Based on the data collected, it was possible to structure the educational product in E-book format, which presents the possibilities of using digital platforms (websites and applications) in reading and writing practices.